An Experimental Analysis of the Complications in Colluding when Firms are Asymmetric - Charles F. Mason (Center for Economic Studies and ifo Institute (CESifo), 2018)
I study an indefinitely repeated game where firms differ in size. Attempts to form cartels in such an environment, for example by rationing outputs in a manner linked to firm size differences, have generally struggled. Any successful cartel has to set production shares in a manner that ensures no firm will defect. But this can require allocating sellers disproportionate shares, which in turn makes these tacit agreements difficult to create and enforce. I analyze some experimental evidence in support of this last proposition.
Keywords: D80; L15; 330; asymmetric cartel; repeated game; experiments